A prospective study to compare clinical and radiological outcomes of functionally versus mechanically aligned knees following robotic total knee arthroplasty - Paul, Amal Antony; THILAK, JAI (The Journal of Knee Surgery)
Introduction: Total knee arthroplasty (TKA) is one of the most effective treatment options for patients with end-stage osteoarthritis (OA) of the knee. However, one out of five patients remain unhappy with the outcomes. In the recent years, more emphasis has been given to knee alignment approaches as a potential solution. The main objective of this study was to compare the clinical and functional outcomes between patients undergoing robot-assisted TKA using mechanical alignment (MA) or functional alignment (FA). Materials and Methods: This prospective non-randomized study enrolled 40 patients (20 patients in each group). The procedure was performed by a single surgeon using FA or MA. In addition to other measures, the New Knee Society Score (NKSS) and Oxford Knee Score (OKS) and modified forgotten joint scores (MFJS) were recorded and the patients were followed-up until 18 months. Results: The baseline characteristics including age, gender, and body mass index, did not differ statistically between the groups. All parameters of the NKSS, the OKS, and the MFJS were improved consistently at all post-operative time-points from 6 weeks through 18 months in the FA-TKA group. The pain score and time to straight leg raise were better in the FA-TKA versus MA-TKA group (P<0.001). Conclusions: Our study showed that FA with robot-assisted TKA was associated with improvement in clinical outcomes and reduced pain. The patients experienced clinically meaningful improvement in patient satisfaction and functional abilities with FA. Due to small sample size of the current study, future studies are needed to confirm these findings.